PENGEMBANGAN DESAIN MOTIF KAIN TENUN GOYOR - Noviani, Leny; Wahida, Adam; Thamrin, AG (Universitas Negeri Yogyakarta, 2015)
The purpose of this program are: (1) to create a design motif of wovenfabric